A framework for siting and dispatch of emerging energy resources to realize environmental and health benefits: Case study on peaker power plant displacement. (September 2016) - Krieger, Elena M.; Casey, Joan A.; Shonkoff, Seth B.C.
Abstract: Emerging grid resources such as energy storage and demand response have the potential to provide numerous environmental and societal benefits, but are primarily sited and operated to provide grid-specific services without optimizing these co-benefits. We present a four-metric framework to identify priority regions to deploy and dispatch these technologies to displace marginal grid air emissions with high environmental and health impacts. To the standard metrics of total mass and rate of air pollutant emissions we add location and time, to prioritize emission displacement near densely populated areas with poor air quality, especially at times when air pollutant concentrations exceed regulatory standards. We illustrate our framework with a case study using storage, demand response, and other technologies to displace peaker power plants, the highest-rate marginal emitters on the California grid. We combine spatial-temporal data on plant electricity generation, air quality standard exceedance days, and population characteristics available from environmental justice screening tool CalEnviroScreen 2.0 to determine where emissions reductions may have the greatest marginal benefit. This screening approach can inform grid siting decisions, such as storage in lieu of peaker plants in high impact regions, or dispatch protocol, such as triggering demand response instead of peaker plants on poor air quality days. Abstract : Highlights: We develop a health and environmental framework for siting clean energy resources. Metrics include total mass, time, rate and location of displaced marginal emissions. Emission displacement is prioritized near dense populations on poor air quality days. We apply our framework to the displacement of peaker power plant generation in CA. We identify optimal places and times to site and dispatch storage and demand response.